Lying under the Mango Tree: Autobiography, Teacher Knowledge and Awareness of Self, Language and Pedagogy - Telles, João A. (The ESPecialist, 2012)
This paper introduces “self-narrative” as a qualitative, autobiographical approach to the study of teacher knowledge and for raising teachers’ critical awareness of self, language and pedagogy. The author explains the meanings and illuminates potential connections among the relevant themes that emerge from stories about his experiences as a person and a teacher of languages. A synthesis (“composite portrait”) of the essential descriptions and meaningful interpretations of these experiences in becoming a teacher and teacher educator is, then, related to self, language and pedagogy.